Antagonistic Functionalized Nucleation and Oxidative Degradation in Combustive Formation of Pyrene‐Based Clusters Mediated by Triplet O and O2: Theoretical Study. Issue 12 (26th June 2015) - Maranzana, Andrea; Tonachini, Glauco
Abstract Polycyclic aromatic hydrocarbons (PAHs) and carbonaceous nanoparticles can be oxidized right from their inception and all through their growth. Oxidation can also promote their degradation. This modelistic density functional theory (DFT) study explores, in a descriptive manner, if oxidation can mediate the earliest stages of nucleation ("functionalized nucleation"), though contrasted by mass declension triggered by oxidation itself. Initial O (3P) attack onto pyrene, chosen as a representative of a generic small PAH or nascent soot lamella, forms an oxyl diradical intermediate that can evolve into an open‐shell epoxide, phenol, or ketone species or, alternatively, undergo mass depletion from the beginning (without impeding further additions). Open‐shell intermediates can add O or O2 (3Σg−) and ethyne, in any order, and open the way, through formation of carbon and oxygen bridges, to the addition of a second molecule of pyrene, whereas formation of direct carbon–carbon links between the two PAH‐like parts might also occur.